Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T12:58:22+01:00
A)2(x-3y)^2-3(x-2y)(x+2y)+12xy dla x=3 i y=-1

2(x²-6xy+9y²)-3(x²-4y²)+12xy = 2x²-12xy +18y²+(-3x)²+12y²+12xy = (-x)² +30 y² =9 + 30 =39

b) (x+3y)(x-3y) + (x+2y)^2 - (2x^2-5y^2) dla x= pierwiastek z 8 i y= pierwiastek z 2

(x+3y)(x-3y) + (x+2y)^2 - (2x^2-5y^2)= x²- 9y² + x² +4xy + 4y² - 2x² + 5y² = 4xy = 4* √8*√2 = 4*√16 =16 lub -16
3 2 3
2010-01-24T13:09:12+01:00
A) 2(x-3y)^2-3(x-2y)(x+2y)+ 12xy= (2x-6y)^2-3(xkwadrat+2xy-2xy-4ykwadrat)+12xy= 4x-12y-3xkwadrat+12ykwadrat+12xy= 4x-12y-3xkwadrat+12ykwadrat+12xy= 4^3-12^(-1)-3^3kwadrat +12^(-1)kwadrat+12^3^(-1)= 12+12-3^9+12-36= 24-27-24+-27

b) (x+3y)(x-3y)+(x+2y)^2-(2x^2-5y^2)= xkwadrat-3xy+3xy-9ykwadrat+2x+4y-10x-10y= xkwadrat-9ykwadrat-8x-6y= (pierwiastek z 8)kwadrat -(pierwiastek z 2)kwadrat -8^pierwiastek z 8-6^pierwiastek z 2=8-2-8pierwiastek z 8-6pierwiastek z 2=6-8pierwiastek z 8-6pierwiastek z 2
1 1 1